The implementation of current guidelines regarding the treatment of cardiovascular risk in type 2 diabetics - Pinchevsky, Yacob (My University, 2012)
Background: Type 2 diabetes mellitus (T2DM) is defined by an increase in serum glucose, however, this leads to the belief that only the serum glucose levels need be monitored and treated. Hence many other risk factors such as obesity, lipids and blood pressure which increase the risk of coronary heart disease, myocardial infarction, stroke and peripheral vascular disease are neglected. Consequently, T2DM patients that are at greater risk of developing cardiovascular disease (CVD), are often not receiving optimal comprehensive care. Aims: To identify the treatment gaps of cardiovascular risk factors in patients with T2DM using both national and international current treatment guidelines. Methods: Using a public sector database, data was obtained on the treatment of 666 T2DM patients. Records of patients were selected on the basis of established T2DM diagnoses, receiving oral hypoglycaemic and/or insulin therapy. The following patient data was recorded: demographics (age, gender, ethnicity), systolic blood pressure (SBP), diastolic blood pressure (DBP), glycated haemoglobin (HbA1c), total cholesterol (TC), triglycerides (TG), HDL-cholesterol (HDL-C), LDL-cholesterol (LDL-C) , family history, cardiovascular history and all chronic medications. The following parameters were applied to the cohort: SBP <130 mmHg, DBP <80 mmHg. In the event of proteinuria: SBP ≤120 mmHg, DBP ≤70 mmHg. HbA1c <7.0%, TC <4.5 mmol/L, LDL-C <2.5 mmol/L, HDL-C >1.0 mmol/L (males), HDL-C >1.2 mmol/L (females) and TG <1.7 mmol/L. In patients with established CVD, LDL-C target: ≤1.8 mmol/L. Results: The study cohort consisted of 666 T2DM-patients. 55% females. Mean age was 63 years (SD: 11.8), mean HbA1c was 8.7% (SD: 2.4). The mean SBP and DBP readings for the cohort were 133.66 (SD: 19.9) and 78.07 mmHg (SD: 11.6), respectively. Mean LDL-cholesterol was 2.6 mmol/L (SD: 0.9). 26.2% reached HbA1c of ≤7%, 45.8% reached ≤130/80 mm Hg blood pressure targets, 53.8% reached LDL-C of ≤2.5mmol/L and all 3 were reached by 7.5% of the cohort. TC ≤4.5 mmol/L was reached by 53.8%, 60.2% reached TG ≤1.7mmol/L, 58.6% males and 52.8% females reached HDL-C targets of ≥1.0 mmol/L and ≥1.2 mmol/L, respectively. There were 17.9% of patients with CVD reaching targets of LDL-C ≤1.8 mmol/L whilst 16.4% of patients with nephropathy reaching targets of ≤120/70 mm Hg. Almost half (48.2%) were not receiving lipid-lowering therapy, yet would be deemed eligible for therapy. Blood pressure targets may have been better reached with appropriate dosage reductions in addition to the introduction of further antihypertensive combination therapy. CVD was present in 15.5%. Conclusions: T2DM patients are at high-risk for CVD. Many trials have demonstrated the benefits of targeting CVD risk factors (HbA1c, blood pressure, serum lipids) in T2DM. Less than 10% of CVD risk factor targets were reached by the study cohort despite treatment guideline recommendations. The data from the study suggests poor control of modifiable cardiovascular risk factors and significant under treatment of T2DM in clinical practice. Whether improvement lies in the form of therapeutic titration adjustment or an increase in patient education, there needs to be a more aggressive multi-factorial therapeutic approach to treating this high risk group of patients in order to reduce overall morbidity, mortality and improve patient outcomes.
Keywords: Diabetes Mellitus, Non-Insulin Dependent; Cardiovascular Diseases